1994
DOI: 10.1111/j.1365-2583.1994.tb00174.x
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of secondary spread by putative clones of Sitobion avenae within a Hampshire wheat field using the multilocus (GATA)4 probe

Abstract: Grain aphids (Sitobion avenae (F.)) were collected from forty-four wheat ears in a Hampshire field at three times during the growing season. On each occasion, individual aphids were profiled using the multilocus (GATA)4 probe. During the full head emergence and full anthesis growth stages of wheat, each ear generally supported a genetically distinguishable aphid colony which consisted of genetically indistinguishable individuals (putative clones). This information strongly suggests that individual ears were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…Winged aphids are important for S. avenae population dynamics during a large part of the season ( Fievet et al , 2007 ) due to their high migration capacity over large distance, but also due to local movements. In addition, apterous S. avenae showed a high disposition to move between plants within fields ( Dean, 1973;Holmes, 1988;DeBarro et al , 1994 ); thus, migration may explain the time-dependent differentiation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Winged aphids are important for S. avenae population dynamics during a large part of the season ( Fievet et al , 2007 ) due to their high migration capacity over large distance, but also due to local movements. In addition, apterous S. avenae showed a high disposition to move between plants within fields ( Dean, 1973;Holmes, 1988;DeBarro et al , 1994 ); thus, migration may explain the time-dependent differentiation.…”
Section: Discussionmentioning
confidence: 96%
“…Aphid populations in cereal fields are regulated by a range of natural enemies, such as predators, parasitoids and fungal pathogens, which all exert a potential selection pressure on the aphids ( Heie, 1980;DeBarro et al , 1994 ). In temperate regions, entomophthoralean fungi, most commonly Conidiobolus obscurus (Hall et Dunn) Remaudière et Keller, Entomophthora planchoniana Cornu and Pandora neoaphidis (Remaudière et Hennebert) Humber, are often observed infecting grain aphids with prevalences possibly exceeding 75% ( Steenberg & Eilenberg, 1995;Plantegenest et al , 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…As for competition, the population density of S. avenae in wheat crops during the sampling season was low; hence, direct clonal competition for feeding sites was unlikely, although evidence for such competition has been found in other studies of this aphid (eg De Barro et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of selection, proliferation of specific clones, spatially and temporally, may well be dictated by differences in local microclimate (eg temperature, humidity), wheat cultivar, crop density and possibly insecticide regime (Carter et al, 1980;Lowe, 1980Lowe, , 1981 Genetic structure in grain aphids at the field scale KS Llewellyn et al Honek, 1987; see also De Barro et al, 1994Fenton et al, 2003). Although insecticide resistance has not, to date, been reported in S. avenae, it has evolved in several other aphid species, including most recently in the greenbug, Schizaphis graminum (Rondani) (Homoptera: Aphididae) (Ono et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…This apparent adaptation breaks down later in the season, probably as the frequency of local movements increases, both within a ¢eld and between ¢elds leading to a lowering of the distinction between the host-adapted clones. However, within a ¢eld, certain genotypes (clones) can colonize greater areas, possibly because of increased adaptive performance, and hence clonal variation declines (De Barro et al 1995a). Shufran et al (1991) also using a method of DNA ¢ngerprinting, showed that populations of the cereal aphid, the greenbug, Schizaphis graminum, in the USA had numerous genotypes but none was unique at any spatial scale from ¢eld to county level.…”
Section: (B) Biotic Factors A¡ecting Redistribution (I) Energy Resourcesmentioning
confidence: 99%